One step pre-hardening micropropagation of Bambusa balcooa Roxb. - Bharat Gami, Nisha Patel, Vipul Bariya., Beena Patel (Journal of Phytology, 2015)
Bamboo’s fast growth and ability to sequester atmospheric carbon consequently mitigate climate change.Abellon’s mission is to reduce CO2 from the environment by growing bamboo on marginal land and using this biomass for bioenergy. Bambusa balcooa Roxb. micropropagation protocol is established for a consistent supply of quality plantlets. Surface sterilization of nodal explants using 0.1% mercuric chloride followed by initiation in liquid and solid media with and without Gentamycin (3.0-8.0 mg/L) containing Murashige and Skoog (MS) media supplemented with 0.01% myo-inositol, 3% sugar, 25 mg/L citrate 50 mg/L ascorbate, and 3.5 mg/L 6-benzylaminopurine (BAP) as growth regulator. Shoots were multiplied using MS medium augmented with 3% sugar, 6% agar, 0.01% myo-inositol with 3 mg/L BAP and 0.5 mg/L naphthalene acetic acid (NAA). Shoot clusters were rooted in MS supplemented with 4 mg/L NAA, pre-hardened in half MS, acclimatized using coco peat, and vermicompost while at net house using vermicompost, soil, sand, and vesicular arbuscular mycorrhiza (VAM) culture. 97% bud break was achieved from initiation while overall success ratio for establishment was 85%. Sub-culturing shoots showed proliferation rate of 3.5-fold. Rooting was successfully achieved with 83% rate.Acclimatization rate at primary and secondary hardening was 72%. The uniqueness of the study lies as bamboo confines to tropical region, however; we have described B. balcooa mass multiplication protocol using explants from arid region with one step pre-hardening process. The protocol achieved multiplication rate of 3.5-fold, overall survival rate 74.66% using vermicompost and VAM for acclimatization of B. balcooa.